2006
DOI: 10.1016/j.molcel.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Regulation in the Na+/Ca2+ Exchanger Involves Two Markedly Different Ca2+ Sensors

Abstract: The plasma membrane Na+/Ca2+ exchanger (NCX) is almost certainly the major Ca2+ extrusion mechanism in cardiac myocytes. Binding of Na+ and Ca2+ ions to its large cytosolic loop regulates ion transport of the exchanger. We determined the solution structures of two Ca2+ binding domains (CBD1 and CBD2) that, together with an alpha-catenin-like domain (CLD), form the regulatory exchanger loop. CBD1 and CBD2 are very similar in the Ca2+ bound state and describe the Calx-beta motif. Strikingly, in the absence of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
254
4
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(277 citation statements)
references
References 61 publications
11
254
4
8
Order By: Relevance
“…Furthermore, the NCX1-Phe-407 may interact with PP1-Met-290. The conformation of the KVFF motif in this model is similar to the conformation of the homologous KIFF motif, as found in the NMR and x-ray structures of the Canis Lupus NCX1 (Protein Data Bank code 2FWS (42) and Protein Data Bank code 2DPK (49)). …”
Section: Pp1c Anchors To the Ncx1-kiff/kvff Motif In Cbd1-pp1supporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the NCX1-Phe-407 may interact with PP1-Met-290. The conformation of the KVFF motif in this model is similar to the conformation of the homologous KIFF motif, as found in the NMR and x-ray structures of the Canis Lupus NCX1 (Protein Data Bank code 2FWS (42) and Protein Data Bank code 2DPK (49)). …”
Section: Pp1c Anchors To the Ncx1-kiff/kvff Motif In Cbd1-pp1supporting
confidence: 70%
“…The first site, RVFF, is localized within the cytosolic loop connecting TM3 and -4. The second site, KIFF/KVFF (human and mouse/rat), is localized in the large cytosolic loop in the first Ca 2ϩ binding domain (CBD1), the primary sensor of calcium (42). The KIFF/ KVFF site does not overlap with the sites in CBD1 that coordinate the four Ca 2ϩ ions (43).…”
Section: Bioinformatic Analysis To Identify Pp1-binding Sites In Ncx1-mentioning
confidence: 99%
“…Structural studies clearly demonstrated that CBD domains do not undergo significant conformational changes upon Ca 2ϩ binding (7)(8)(9), although some specific (yet unidentified) electrostatic interactions of Ca 2ϩ with CBD sites may drive functionally important reorientation of two CBD domains (17,26,(33)(34)(35) sites of CBD1 are separated by 3-4 Å) and exhibit positive cooperativity for Ca 2ϩ binding despite the strong charge repulsion between the adjacent divalent cations (16,17,25,26,(33)(34)(35). The close adjacencies of Ca 2ϩ sites in CBDs (7)(8)(9)33) is consistent with a sharp dependence of Ca 2ϩ binding on pH (36 -38). The binding of the first Ca 2ϩ ion to CBD may partially (or fully) deprotonate the coordinating residue(s), thereby enabling the next Ca 2ϩ ion to bind to the remaining site(s).…”
Section: Discussionmentioning
confidence: 99%
“…The allosteric effect depends on Ca 2ϩ binding to a site that itself does not produce translocation but regulates transport kinetics. The cytosolic loop of NCX includes two closely spaced domains named Ca 2ϩ binding domain 1 (CBD1) and CBD2 (7)(8)(9), each of which share a common core structure typical of C 2 -type domains (10,11). Such C 2 domains are known to interact with diverse effectors (e.g.…”
mentioning
confidence: 99%
“…ϩ /Ca 2ϩ exchanger (NCX1-3) 4 proteins extrude Ca 2ϩ , an essential signaling molecule, from the cell. Their activity is strongly and allosterically regulated by the interaction of Ca 2ϩ with regulatory sites on the exchanger (1,2).…”
Section: Mammalian Namentioning
confidence: 99%